Impact assessment of Dan Kia inflows and application aquatox model in managing water quality - Tinh, Tran Thi; Hai, Doan Nhu; Lam Ha, Bui Nguyen; Thanh Thuan, Nguyen Thi (Academia Journal of Biology, 2016)
The parameters used for measuring water quality of Dan Kia reservoir were temperature, pH, conductivity, secchi disk depth, dissolved oxygen (DO), chlorophyll a, nutrients: nitrogen (ammonia, nitrate) and phosphate. There are five influents for the reservoir, therefore the water quality of Dan Kia reservoir depends on activities around these channels. S1 stream has the highest flow into the reservoir (8.2×106m3/year) but most of the nutrients were discharged from S4 and S5 stream. Concentration of ammonia, nitrate and phosphate from these channels is accounting for 89.82, 58.15 and 57.16% into the lake, respectively. The study constructed three scenarios and run them using AQUATOX model. The first scenario, all existing inflows are discharging into the lake, present situation. The second scenario, none is discharging. The third scenario, all are discharging except S4 stream and S5 stream. The result from the first scenario showed that the concentrations from the model consistent with measurements in the reservoir. In case the second and third scenarios happened the concentrations considerably decreased.